1983
DOI: 10.1088/0031-9155/28/3/003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tungsten absorption edge filter on diagnostic x-ray spectra, image quality and absorbed dose to the patient

Abstract: The X-ray spectra from a tungsten-target diagnostic tube were measured with a lithium-drifted silicon detector. Four characteristic X-ray peaks were clearly observed. When a 0.05-0.3 mm thick tungsten absorption edge filter was added to the tube, the number of photons in the spectra above the K-absorption edge decreased dramatically. The effect of the absorption edge filter on image quality and on the absorbed dose were investigated by both measurement and Monte Carlo calculation. The absorbed dose to the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In previous studies using W filters, which increased the overall image quality, the entrance dose decreased from 22% to 15%, and the overall image quality was more uniform [ 17 ]. Other studies have also reported that the addition of a 0.1mm W filter reduced the total absorbed dose by 0.73 times and did not reduce the overall image quality [ 15 ]. Additionally, a study has reported that the W filter, which is the bandwidth filter, reduced the radiation exposure of patients by >50% compared to the Al filter without decreasing the image quality [ 5 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies using W filters, which increased the overall image quality, the entrance dose decreased from 22% to 15%, and the overall image quality was more uniform [ 17 ]. Other studies have also reported that the addition of a 0.1mm W filter reduced the total absorbed dose by 0.73 times and did not reduce the overall image quality [ 15 ]. Additionally, a study has reported that the W filter, which is the bandwidth filter, reduced the radiation exposure of patients by >50% compared to the Al filter without decreasing the image quality [ 5 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The radiation dose and image quality should be optimized to balance the patient dose with the radiographic image quality, which is determined by tube voltage and additional filtration [ 5 , 11 , 12 , 13 ]. Although not all photons contribute to image formation, most low-energy photons, which are absorbed by the patient and do not contribute to the formation of images, have been studied for selective removal of high-energy photons [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A high intensity scanning point source (for longitudinal scan at each rotational step) or a stationary line source can be used. Our choice is to use an x-ray tube to provide filtered x-rays or characteristic x-rays when a heavy-element is irradiated [39], [40]. In both cases, the transmission flux is reduced in intensity and centers on a narrow energy band suitable for photon counting detection.…”
Section: C-spect-imentioning
confidence: 99%
“…Historically, dose reduction through the use of filters has involved compromises among different types and thicknesses of filter materials, the effects on image quality from changes in the x-ray beam spectra, and considerations of additional tube loading which impact tube life, focal spot size, and exposure times. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Regulatory and advisory agencies have responded by issuing requirements or guidelines setting forth minimum filtration standards. [17][18][19][20] Although the skin entrance dose decreases fairly rapidly with increasing filtration ͑with the kVp and exit dose held constant͒ this is generally not the case for most organs.…”
Section: Introductionmentioning
confidence: 99%